Low Level Laser Therapy for Painful Joints - Momenzadeh, Sirous (Journal of Lasers in Medical Sciences, 2013)
Low Level Laser Therapy (LLLT) uses a light source that generates extremely pure light, of a single wavelength1. The effect is not thermal, but rather related to photochemical reactions in the cells. LLLT was introduced as an alternative non-invasive treatment for OA about 10 years ago, but its effectiveness is still controversial2. A Cochrane review of LLLT in osteoarthritis included five trials, and concluded that despite some positive findings, the meta-analysis lacked data on how LLLT effectiveness was affected by the important factors of wavelength, treatment duration of LLLT, dosage, and site of application over nerves instead of joints1,3,4,5,6,7. A different review2 addresses some of these issues in a wider range of trials, and is broadly positive, if limited by numbers.